Social Representations of the African Other among participants of a Global Citizenship course in the Netherlands - Koeijer, Valerie de; Park, Eri; Sklad, Marcin (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This study aims to demonstrate processes by which Going Glocal, a Global Citizenship educational program based on Postcolonial Theory, can challenge social representation of the African Other among participating students. Postcolonial Theory argues that the colonial history of countries directly affects the current state of previously colonized countries and contemporary relations between people from Europe and Africa. Critical Whiteness Theory is concerned with the privileged position of a white self, for whom these privileges usually do not become tangible. 15 university college students traveled to Namibia as part of 2012 Going Glocal project and semi-structured interviews were conducted with them directly after they came back, as well as focus groups at the very beginning and end of the program. Two students with opposite socio-economic and ethnical backgrounds were selected for this case study. Their responses were interpreted using Social Representations Theory as a theoretical framework, to reveal the divergent positioning the interviewees took, and were analyzed according to Postcolonial and Critical Whiteness Theory.